2017
DOI: 10.5946/ce.2017.045
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Management of Pancreatic Fluid Collections: Update and Review of the Literature

Abstract: Severe acute pancreatitis is often complicated by the development of pancreatic fluid collections (PFCs), which may be associated with significant morbidity and mortality. It is crucial to accurately classify these collections as a pseudocyst or walled-off necrosis (WON) given significant differences in outcomes and management. Interventions for PFCs have increasingly shifted to less invasive strategies, with endoscopic ultrasound (EUS)-guided methods being shown to be safer and equally effective as more invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 55 publications
1
74
0
2
Order By: Relevance
“…Significant procedural morbidity and mortality has been reported; hence percutaneous and endoscopic drainage techniques have overtaken traditional open approaches to pancreatic pseudocysts. Compared to surgery, randomized control trials have confirmed that an endoscopic approach is safer and associated with lower costs, shorter hospital stay, and improved quality of life . Owing to its heterotopic position and jejunal drainage, endoscopic drainage often is not technically feasible/accessible in the transplant pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant procedural morbidity and mortality has been reported; hence percutaneous and endoscopic drainage techniques have overtaken traditional open approaches to pancreatic pseudocysts. Compared to surgery, randomized control trials have confirmed that an endoscopic approach is safer and associated with lower costs, shorter hospital stay, and improved quality of life . Owing to its heterotopic position and jejunal drainage, endoscopic drainage often is not technically feasible/accessible in the transplant pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for intervention in native pancreatic pseudocysts include infected pseudocysts, symptoms related to the pseudocyst size or position, and failure to regress. Size on its own is seldom a sole indication to intervene . We performed cystojejunostomy on 1 patient due to failure of repeated percutaneous drainage attempts and documented communication with the main pancreatic duct (patient 20).…”
Section: Discussionmentioning
confidence: 99%
“…Another fact that should be taken into account is the existence of submucosal vessels or true varicose veins that are not infrequently associated and that may be interposed between the gastric wall and the cyst. The use of color Doppler helps to identify these structures and maneuver the echoendoscope in order to avoid them when it comes to puncture (26).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the right time to perform endoscopic intervention is after 4 weeks as it allowed better encapsulation. Recent systematic review, comparing percutaneous, surgical, and endoscopic methods in managing PPC, shows that endoscopic management using EUS reduced the length of hospital admission time, cost, and improved patient's quality of life [21,22].…”
Section: Endoscopic Management Of Pancreatic Fluid Collection: Histormentioning
confidence: 99%